REDESAIN BANGUNAN TAHAN GEMPA HOTEL 6 LANTAI DI WILAYAH YOGYAKARTA BERDASARKAN SNI GEMPA 1726:2019 - Vannysa Zian Mara Yogita; Endah Kanti Pangestuti (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2023)
The Province of the Special Region of Yogyakarta is one of the parts affected by the natural earthquake due to being passed by three tectonic plate meeting points, namely the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate. As a result, the surrounding high-rise buildings were damaged. The 6-storey hotel building in Yogyakarta was opened in 2019 referring to the earthquake SNI. The plan for this building will be designed based on SNI 1726:2019 concerning Procedures for Planning Earthquake Resistance for Building and Non-Building Structures and SNI 2847:2019 Requirements for Structural Concrete for Buildings and Non-Building Structures using Etabs v.20.0 software. After the redesign process was carried out, it resulted in changes to the spectrum response graph in SNI 1726: 2019 article 6.4, the seismic force response spectrum controlled by an equivalent static earthquake in SNI 1726: 2019 article 7.9.1 and article 7.9.2.5.2 resulted in a scale factor of 2.182 m/ s2 and do not experience deviations between levels. There are changes in the dimensions of the beams, changes in the longitudinal and transverse reinforcement in the beams and columns, and there are changes in the spacing of the reinforcement in the beams, columns, and floor slabs.